The house of cross ebook - Patterson, James (Alex Cross, 2024)
Supreme Court candidates are being murdered—and only Alex Cross and John Sampson can take the case in  The House of Cross.  “[Alex Cross’s] innate nature is to protect people…If he has a weakness, it’s his family, especially his children. They’re the chink in his armor. But aside from that, it’s tough to get at him.”  –Aldis Hodge, star of Cross on Prime Video In Washington, DC, the president-elect is planning her inauguration. The list of Supreme Court candidates is highly confidential—until it becomes evidence in Detective Alex Cross’s toughest investigation. One candidate is gunned down. A second is stabbed. A third is murdered near midnight on a city street.   Cross is the FBI’s top expert in criminal behavior. For the sake of his family, his city, and his country, he must put himself in the most dangerous place there is: inside the mind of a diabolical killer.